Kemampuan pemecahan masalah mahasiswa pada mata kuliah kalkulus diferensial - Mayang Gadih Ranti; Indah Budiarti (STKIP PGRI Banjarmasin, 2018)
This research aims to describe problem solving abillity of mathematics education departement students STKIP PGRI Banjarmasin in the academic year 2017/2018 on differential calculus. The populations of research were 21 of differential calculus students in the academic year 2017/2018. This research was a Total sampling Population Research. The research method was a descriptive method. Data Collection Technique was a test. The research instrument was a problem solving abillity test on maximum-minimum problem topic. Data was analyzed by using averages and percentages. The study found that problem solving abillity of students on differential calculus is in the middle level.